Heritage Stone 6. Gneiss for the Pharaoh: Geology of the Third Millennium BCE Chephren’s Quarries in Southern Egypt - Heldal, Tom; Storemyr, Per; Bloxam, Elizabeth; Shaw, Ian (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2016)
A remarkable campaign of decorative stone quarrying took place in the southwestern Egyptian desert almost 5000 years ago. The target for quarrying was Precambrian plagioclase−hornblende gneiss, from which several life-sized statues of King Chephren (or Khafra) and thousands of funerary vessels were produced. The former inspired George Murray in 1939 to name the ancient quarry site 'Chephren's Quarries.' Almost 700 individual extraction pits are found in the area, in which free-standing boulders formed by spheroidal weathering were worked by stone tools made from local rocks and fashioned into rough-outs for the production of vessels and statues. These were transported over large distances across Egypt to Nile Valley workshops for finishing. Although some of these workshop locations remain unknown, there is evidence to suggest that, during the Predynastic to Early Dynastic period, the permanent settlement at Hierakonpolis (Upper Egypt) could have been one destination, and during the Old Kingdom, another may have been located at pyramid construction sites such as the Giza Plateau (Lower Egypt). Chephren's Quarries remains one of the earliest examples of how the combined aesthetic appearance and supreme technical quality of a rock made humans go to extreme efforts to obtain and transport this raw material on an 'industrial' scale from a remote source. The quarries were abandoned about 4500 years ago, leaving a rare and well-preserved insight into ancient stone quarrying technologies.